Modeling Dimensions of Prosodic Prominence - Roessig, Simon; Mücke, Doris (Frontiers in Communication, 2019)
Detailed modifications both in the laryngeal as well as in the supra-laryngeal domain have been shown to be used by speakers of German to express prosodic prominence. This paper aims to bring the two domains together in a joint analysis and modelling account. We report results on the prosodic marking of focus types from 27 speakers that were recorded acoustically and with electromagnetic articulography. We investigate the intonational patterns (tonal onglide) as well as the articulatory movements during the vowel production (lip aperture and tongue body position). We provide further evidence for categorical and continuous modifications across and within accentuation and sketch a dynamical model that accounts for these modifications on multiple dimensions as the consequence of scaling the same parameter. In this model, the prosodic dimensions contribute differently to the complex shape of the compositional attractor landscape and respond differently to the scaling of the system. The study aims to add to our understanding of the integration of speech sounds in a two-fold manner: the integration of different channels of prosody (laryngeal and supra-laryngeal) as well as the interplay of categorical and continuous aspects of speech.